Implementação de modelo de melhoria de processos no Centro Regional Sul de Pesquisas Espaciais, na área de tecnologia de informação, baseado no CMM - Ozaki, Koiti (2007)
This work presents a proposition to an improvement process model implementation in Southern Regional Space Research Center, into Information Tecnology area, applying the recommendations of Capability Maturity Model (CMM) and pursuing to reach the level 2 of maturity of this model in time of 24 months.